2022
DOI: 10.3390/ijms23031126
|View full text |Cite
|
Sign up to set email alerts
|

Roux-En-Y Gastric Bypass (RYGB) Surgery during High Liquid Sucrose Diet Leads to Gut Microbiota-Related Systematic Alterations

Abstract: Roux-en-Y gastric bypass (RYGB) surgery has been proven successful in weight loss and improvement of co-morbidities associated with obesity. Chronic complications such as malabsorption of micronutrients in up to 50% of patients underline the need for additional therapeutic approaches. We investigated systemic RYGB surgery effects in a liquid sucrose diet-induced rat obesity model. After consuming a diet supplemented with high liquid sucrose for eight weeks, rats underwent RYGB or control sham surgery. RYGB, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…45 It was also established that changes in the intestinal microflora affect the ENS and lead to changes in the secretion of neurotransmitters through gut-brain communication. 46 It was also possible that changes in the neurochemical coding of the ENS neurons noted in the present study are the result of glyphosateinduced changes in the microbiome, but this issue requires further research.…”
Section: Discussionmentioning
confidence: 80%
“…45 It was also established that changes in the intestinal microflora affect the ENS and lead to changes in the secretion of neurotransmitters through gut-brain communication. 46 It was also possible that changes in the neurochemical coding of the ENS neurons noted in the present study are the result of glyphosateinduced changes in the microbiome, but this issue requires further research.…”
Section: Discussionmentioning
confidence: 80%
“…Another common effect of RYGB surgery is to alter the gut microbiota and its related metabolites. Escherichia Coli, Streptococcus, pneumonia, Klebsiella, Akkermansia muciniphila, Dentium, and Bifidobacterium in the feces of patients increased after RYGB surgery [42]. After RYGB surgery, there is a decrease in Firmicutes and an increase in the frequency of Verrucomicrobia (Akkermansia) and proteobacteria in patients.…”
Section: Effects Of Bariatric Surgery Methods On Gut Microbiota 41 Ro...mentioning
confidence: 92%
“… Brooks et al (2016) used targeted free fatty acid receptor 2 (FFAR2)-deficient mice and intestinal organoids to explore the mechanism in vivo and found that FFAR2 signalling drives the expansion of the PYY cell population, resulting in increased PYY secretion, which in turn increases the intestinal anorexia signalling. After Roux-en-Y gastric bypass surgery (RYGB) operation on obese mice, the intake of food and liquid sucrose decreased, and the intestinal flora, faecal metabolites, fat distribution in plasma, and brain neuron activity of obese mice changed after operation ( Zizmare et al, 2022 ). Obese patients with diabetes have reduced food intake after RYGB due to increased postoperative levels of GLP-1 and PYY, which stimulate insulin secretion and reduce patient appetite after ingesting food ( Goldspink et al, 2020 ).…”
Section: Construction and Application Of Intestinal Organoidsmentioning
confidence: 99%